2016
DOI: 10.3917/redp.261.0057
|View full text |Cite
|
Sign up to set email alerts
|

Finance and International Trade: A Review of the Literature

Abstract: The aim of this paper is to review the literature on the link between finance and international trade. First, export performance is shown to strongly depend on sectors' or firms' external finance dependence. More vulnerable firms or sectors export less than others. Moreover, insufficient financial development and financial crises harm exports to a greater extent when firms or sectors are dependent on external finance. Second, trade finance plays a key role in financing trade and provides a powerful transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…Consistent with this stance, the results from Berman and Héricourt's ( 2010) study on the effects of financial characteristics on export levels proves the insignificant impact of the leverage ratio, the liquidity ratio, and collateralizable assets on the quantity of exports. Overall, the empirical evidence supports the theoretical literature that a financial crisis intensifies the negative effects of financial constraints on foreign trade (Vaubourg 2016).…”
Section: The Effect Of Financial Development On Foreign Trade - the Esupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with this stance, the results from Berman and Héricourt's ( 2010) study on the effects of financial characteristics on export levels proves the insignificant impact of the leverage ratio, the liquidity ratio, and collateralizable assets on the quantity of exports. Overall, the empirical evidence supports the theoretical literature that a financial crisis intensifies the negative effects of financial constraints on foreign trade (Vaubourg 2016).…”
Section: The Effect Of Financial Development On Foreign Trade - the Esupporting
confidence: 79%
“…The first theoretical underpinning that explains the channel through which finance impacts foreign trade is trade finance theory (Vaubourg 2016). Firms involved in foreign trade have a choice among a variety of trade finance options, which include open accounts, cash in advance, letters of credit, and export credit guarantees.…”
Section: The Impact Of Financial Development On Foreign Trade - the Tmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings showed that firms who had better access to any finance were more likely to export and exported more. Vaubourg (2016) provided extensive review of the literature on the links between finance and international trade and found that sectors' or firms' external financial dependence appears to be a key determinant of export performance. Hence, contemporary literature from all over the globe covering large samples of different countries point out various current account determinants of a country with different nature of the relationship between current account of a country and its determinants.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Similarly, while we discuss related empirical work, this discussion in not exhaustive as our primary focus is on quantitative studies that investigate the impact of financial frictions using equilibrium models with heterogeneous firms. Manova (2010), Contessi and De Nicola (2012), Foley and Manova (2015), and Vaubourg (2016) provide complementary coverage of the related empirical literature.…”
Section: Introductionmentioning
confidence: 99%